Collective action and conflict of interests: the case of the peasant community of Catac - Osorio Bautista, Serafín (2013)
This article proposes a comprehension of social changes in the peasant community of Catac as results of collective action in a context where challenges present themselves as political opportunities and social contentions as well as internal demands of interest groups or factions. In an heterogeneous community as Catac, collective action is not something that is taken for granted but it is deliberately created and constituted. However, it tends to be fragile and usually breaks because of outside pressures and the power relations defined as relations among factions that exist in community.